Surface-guided positioning eliminates the need for skin markers in radiotherapy of right sided breast cancer: A single center randomized crossover trial. (December 2022) - Svestad, Jørund Graadal; Heydari, Mojgan; Mikalsen, Stine Gyland; Flote, Vidar Gordon; Nordby, Fredrik; Hellebust, Taran Paulsen
Highlights: Setup of right sided breast cancer patients using surface guidance yields higher accuracy than setup using skin marks/tattoos and lasers. There is no difference in setup time between a surface guided procedure and a skin marker/tattoo based procedure. CBCT should still be used for setup verification. Abstract: Background and purpose: To prospectively investigate whether surface guided setup of right sided breast cancer patients can increase efficiency and accuracy compared to traditional skin marker/tattoo based setup. Material and methods: Twenty-five patients were included in this study. Each patient was positioned using skin marks and tattoos (procedure A) for half of the fractions and surface guidance using AlignRT (procedure B) for the other half of the fractions. The order of the two procedures was randomized. Pretreatment CBCT was acquired at every fraction for both setup procedures. A total of ten time points were recorded during every treatment session. Applied couch shifts after CBCT match were recorded and used for potential error calculations if no CBCT had been used. Results: In the vertical direction procedure B showed significant smaller population based systematic (Ʃ) and random (σ) errors. However, a significant larger systematic error on the individual patient level (M) was also shown. This was found to be due to patient relaxation between setup and CBCT matching. Procedure B also showed a significant smaller random error in the lateral direction, while no significant differences were seen in the longitudinal direction. No significant difference in setup time was found between the two procedures. Conclusion: Setup of right sided breast cancer patients using surface guidance yields higher accuracy than setup using skin marks/tattoos and lasers with the same setup time. Patient alignment for this patient group can safely be done without the use of permanent tattoos and skin marks when utilizing surface-guided patient positioning. However, CBCT should still be used as final setup verification.